(untitled) (Texas Journal of Philology, Culture and History, 2023)
this article shows the effect of atmospheric air on the development of powdery mildew of melon under laboratory conditions. The experiments were conducted at a temperature of 280 C. As a result, there is information about the development of the disease with increasing humidity.